Analisis Penyusunan Program Pembelajaran Tahunan Berdasarkan Tinjauan Distribusi Dan Kompetensi Dasar Penyusunan Prota - Lannuria Lannuria; Junita Karinah; Miftahul Jannah; Nurul Aini; Pahrudin Pahrudin; Wismanto Wismanto (Lembaga Pengembangan Kinerja Dosen, 2024)
We as prospective teachers should know about planning. To facilitate an effective education and learning system, careful planning is needed, including semester programs and annual programs that must be prepared in an educational institution to map out the time allocation for each competency that will be studied during one year and one semester so that time can be used efficiently. effective and efficient. With this need, we will take a sample so that we can all know what a semester program and an annual program are. An annual program is a plan for determining one year's time allocation to achieve the goals of the Competency Standards/Core Competencies and Basic Competencies that have been determined. The annual program contains a description of the time allocation for each competency standard/core competency and basic competency for each semester and each class for one school year. The components of the annual program include identification (education unit, subject, academic year) competency standards, basic competencies, time allocation and information. The aim of this research is to benefit from the annual program (Prota) for teachers and schools so as to facilitate learning activities carried out in schools. to make it easier for teachers to deliver the material that will be delivered according to the JP (Lesson Hours) that have been created.